2003
DOI: 10.1203/01.pdr.0000057204.51420.dc
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Ca2+-Activated Cl− Secretion by Basolateral K+ Channels in Human Normal and Cystic Fibrosis Airway Epithelia

Abstract: Human airway epithelia express Ca2+-activated Cl- channels (CaCC) that are activated by extracellular nucleotides (ATP and UTP). CaCC is preserved and seems to be up-regulated in the airways of cystic fibrosis (CF) patients. In the present study, we examined the role of basolateral K+ channels in CaCC-mediated Cl- secretion in native nasal tissues from normal individuals and CF patients by measuring ion transport in perfused micro Ussing chambers. In the presence of amiloride, UTP-mediated peak secretory respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
93
2
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(101 citation statements)
references
References 47 publications
5
93
2
1
Order By: Relevance
“…Indeed, voltage-dependent K ϩ KvLQT1 channels and calciumactivated K ϩ (K Ca ) channels have been identified as key elements of ion transport. A severe reduction of Cl Ϫ secretion has been reported after inhibition of KvLQT1 and intermediate-conductance, calcium-activated K ϩ (IK Ca ) channels in nasal and bronchial cells (12,34,35). More interestingly, it has been observed that IK Ca channel openers stimulate Cl Ϫ secretion in Calu-3 cells (16,56), in primary cultures of human bronchial epithelia (56), and in nasal cells (35).…”
mentioning
confidence: 99%
“…Indeed, voltage-dependent K ϩ KvLQT1 channels and calciumactivated K ϩ (K Ca ) channels have been identified as key elements of ion transport. A severe reduction of Cl Ϫ secretion has been reported after inhibition of KvLQT1 and intermediate-conductance, calcium-activated K ϩ (IK Ca ) channels in nasal and bronchial cells (12,34,35). More interestingly, it has been observed that IK Ca channel openers stimulate Cl Ϫ secretion in Calu-3 cells (16,56), in primary cultures of human bronchial epithelia (56), and in nasal cells (35).…”
mentioning
confidence: 99%
“…Previous studies showed that (i) application of the Ca 2ϩ ionophore ionomycin also activates Cl Ϫ secretion; (ii) in the presence of low (1 M) extracellular Ca 2ϩ , activation of Cl Ϫ secretion is very transient; (iii) after inhibition of phospholipase C, purinergic Cl Ϫ secretion is reduced; and (iv) DIDS inhibits Ca 2ϩ -activated Cl Ϫ secretion in mouse airways (18). These and other experiments (19) Both CFTR and CaCC control airway surface liquid, which is essential for mucociliary clearance (27). Purinergic activation of CaCC in the airways resembles an important therapeutic principle for cystic fibrosis (28,29).…”
Section: Discussionmentioning
confidence: 63%
“…Cl Ϫ secretion in mouse airways is dominated by CaCC, which explains why CFTR knock-out animals do not develop a cystic fibrosis lung disease (21). Interestingly, a functional relationship exists between CaCC and CFTR (30,31), and Ca 2ϩ -mediated Cl Ϫ secretion is enhanced in cystic fibrosis airways (19). Thus, Ca 2ϩ -activated Cl Ϫ secretion is found in cystic fibrosis but not normal murine nasal epithelium (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…En effet, leur inhibition réduit fortement la sécrétion de Cl -par les cellules des voies aériennes [8,10,19,21]. Inversement, l'activation des canaux KCa3.1, qui stimule la sécrétion de Cl - [19,21], a été proposée comme une stratégie prometteuse pour favoriser le transport de Cl -dans les tissus Fk par des canaux CFTR résiduels ou des canaux Cl -alternatifs ( Figure 3B, Fk).…”
Section: Contrôle Du Transport Transépithélial Ionique Et Liquidienunclassified